2012
DOI: 10.1007/s00420-012-0790-4
|View full text |Cite
|
Sign up to set email alerts
|

Airway irritation among indoor swimming pool personnel: trichloramine exposure, exhaled NO and protein profiling of nasal lavage fluids

Abstract: Purpose Occurrence of airway irritation among indoor swimming pool personnel was investigated.The aim was to assess trichloramine exposure levels and exhaled nitric oxide in relation to the prevalence of airway symptoms in swimming pool facilities and to determine protein effects in the upper respiratory tract. MethodsThe presence of airway symptoms related to work were examined in 146 individuals working at 46 indoor swimming pool facilities. Levels of trichloramine, as well as exhaled nitric oxide, were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 42 publications
6
29
1
Order By: Relevance
“…It is possible that this is related to different functions of the two S100 proteins as, in mice, S100-A8 acts as an activator of Toll-like receptor 4 promoting endotoxin induced inflammation while S100-A9 appear to have a more regulatory role [30]. Notably, the levels of S100-A8 were not significantly altered in the subjects with symptoms although we recently have found decreased levels of S100-A8, but unaltered levels of S100-A9, in swimming pool personnel with similar upper airway symptoms as the MWF exposed workers [31]. This may indicate that a disturbed balance between the two S100 proteins is a common feature of upper respiratory mucosal inflammation.…”
Section: Discussionmentioning
confidence: 69%
“…It is possible that this is related to different functions of the two S100 proteins as, in mice, S100-A8 acts as an activator of Toll-like receptor 4 promoting endotoxin induced inflammation while S100-A9 appear to have a more regulatory role [30]. Notably, the levels of S100-A8 were not significantly altered in the subjects with symptoms although we recently have found decreased levels of S100-A8, but unaltered levels of S100-A9, in swimming pool personnel with similar upper airway symptoms as the MWF exposed workers [31]. This may indicate that a disturbed balance between the two S100 proteins is a common feature of upper respiratory mucosal inflammation.…”
Section: Discussionmentioning
confidence: 69%
“…All of these studies have shown increased ocular and upper respiratory symptoms, and all but the French and Swiss studies [11,15] found increased lower respiratory symptoms in individuals who work at pools. Some studies found a correlation between symptoms and exposure levels of trichloramine [12][13][14]. None of these cross-sectional studies performed peak flow or spirometric measures in association with work, nor did they identify whether individuals with preexisting asthma had more symptoms after beginning work in a pool setting in comparison to before working at a pool.…”
Section: Discussionmentioning
confidence: 93%
“…Six previous cross-sectional studies of swimming pool personnel were identified and are consistent with our finding of aggravation of pre-existing asthma. These studies have been conducted in France [11], Italy [12], the Netherlands [13], Sweden [14], Switzerland [15] and the United States [16]. All of these studies have shown increased ocular and upper respiratory symptoms, and all but the French and Swiss studies [11,15] found increased lower respiratory symptoms in individuals who work at pools.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…8,[14][15][16][17] Hypersensitivities to fungus and mites are aggravated by the time spent within the pool area, which leads to cytological changes. The concentrations of chlorine by-products in indoor air, such as trihalomethanes and trichloramine, have been found to be correlated with the concentrations found in the pool water.…”
Section: Discussionmentioning
confidence: 99%